Earth lab : - Owen, Claudia (Thomson Brooks/Cole, 2006)
Utilizing graphs and simple calculations, this clearly written lab manual complements the study of earth science or physical geology. Engaging activities are designed to help you develop data-gathering skills (e.g., mineral and rock identification) and data-analysis skills. You'll learn how to understand aerial and satellite images; to perceive the importance of stratigraphic columns, geologic sections, and seismic waves; and more